Is Literature Secular? Transsecular Politics of Literature and Hermeneutics of Hospitality - González Blanco, Azucena (Political theology, 2024)
Here I introduce the transsecular concept for the development of a politics of literature in a syncretic, transsecular society. If literature, as per Jacques Rancière (literature as a contradictory discourse in La Parole muette: Essai sur les contradictions de la littérature) and Michel Foucault (madness as principle of social partition in Folie, langage, littérature, 2019) is a laboratory of experiences that makes it possible to think outside of binary logic, through non-dialectic contradiction, which does not transform the dual into the univocal. Then, the transsecular approach aims to articulate these identity differences based on a principle of “hospitable” reading, a transsecular hermeneutics, which is in the very origin of the texts that form literary traditions. This hospitable principle of reading proposes a hermeneutics of literary texts as ethics of the care of the self. The transsecular approach is thus based on a synctretic hermeneutics of texts of both secular and religious origin, which live alongside and set different cultural traditions to dialog with each other, following the model of literature that is by nature really transtextual.